The Relationship Between Work Load, Working Length And Working Posture With Low Back Pain (LBP) Complaints In Convection Tailors In Karawang 2025 - Jihan Azzahra Salsabila; Sudiono Sudiono; Saleh Budi Santoso (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: This study aims to analyze the relationship between workload, working duration, and work posture with low back pain (LBP) complaints in garment tailors in Karawang Regency in 2025. Method: The method used is descriptive analytic with a cross-sectional design, involving 45 respondents. Data were collected through a questionnaire that measured the variables of workload, working duration, working posture, and LBP complaints. Result: The results showed that 77.8% of respondents experienced severe LBP. Bivariate analysis with the Chi-Square test showed a significant relationship between workload (p = 0.029), working duration (p = 0.022), and working posture (p = 0.013) with the incidence of LBP. The odds ratio (OR) for heavy workload was 6.769, working duration >8 hours was 6.000, and very high working posture was 7.250 Conclusion: In conclusion, garment tailors with high workload, working duration more than 8 hours, and non-ergonomic working posture have a higher risk of experiencing LBP. This research is expected to provide insight for convection industry managers to take appropriate preventive measures.